CONTINUITIES AND CHANGES - Ahmad Sabri; Meirison Meirison; Jhoni Warmansyah (IAIN Tulungagung, 2020)
This article discusses continuities and changes of educational institutions during the political transition from the Seljuq dynasty to the Ottoman sultanate. It diachronically examines elements of education which were transformed and adapted into a new political structure under the political regime, the Ottoman. This article will closely look at institutional transformation and educational curricula as to which the changing political regime affected contents and management of Islamic education. This article further argues that the political transformation from the Seljuq to the Ottoman had generated a new educational system in which the Ottoman imposed the attempts to integrate Islam and modern sciences. At managerial level, the transformation has also invited the introduction of science in Islamic educational system. Western educational system reserved as an important reference for this transformation amid the changing regime from the Seljuq to the Ottoman.